Enhancing Customer Loyalty in the Digital Economy: The Role of Service Quality and Satisfaction in Livin' by Mandiri Mobile Banking - Kusmanto, Kusmanto; Islami, Mutiara (International Journal of Economics Development Research (IJEDR), 2025)
This research aims to determine the influence of Service Quality and Customer Satisfaction on Customer Loyalty of Mobile Bangking Livin by Mandiri KCP Tangerang STPI Curug jointly and individually and to determine the variables that have a dominant influence on Customer Satisfaction. The research method used is a causal quantitative approach. The population in this research was 336 customers. The sampling technique used purposive sampling with a total sample of 77 customers obtained using the Slovin formula. Based on the research results, it is proven that service quality has an influence of 54.3% on customer satisfaction, while the remaining 45.7% is influenced by other factors not examined in this research. The results of the F test in this study show that the calculated f value is 43.894 > f table 3.96847 and the sig. F 0.000 < 0.05, which means that Service Quality and Customer Satisfaction together have a positive and significant influence on Customer Loyalty. Based on the results of the T Test, it can be seen that the Service Quality variable partially has a positive and significant influence on Customer Loyalty. Meanwhile, the Customer Satisfaction variable does not have a positive and significant influence on Customer Loyalty. And the largest standard value of the coefficient of determination is the value of the Service Quality variable, namely 0.530, which means that the Service Quality variable has the most dominant influence on Customer Loyalty.